Genome-Wide Discovery of InDel Markers in Sesame (Sesamum indicum L.) Using ddRADSeq - Sibel Kizil; Merve Basak; Birgul Guden; Hilal Sule Tosun; Bulent Uzun; Engin Yol (Plants, 2020)
The development and validation of different types of molecular markers is crucial to conducting marker-assisted sesame breeding. Insertion-deletion (InDel) markers are highly polymorphic and suitable for low-cost gel-based genotyping. From this perspective, this study aimed to discover and develop InDel markers through bioinformatic analysis of double digest restriction site-associated DNA sequencing (ddRADSeq) data from 95 accessions belonging to the Mediterranean sesame core collection. Bioinformatic analysis indicated the presence of 7477 InDel positions genome wide. Deletions accounted for 61% of the InDels and short deletions (1–2 bp) were the most abundant type (94.9%). On average, InDels of at least 2 bp in length had a frequency of 2.99 InDels/Mb. The 86 InDel sites having length ≥8 bp were detected in genome-wide analysis. These regions can be used for the development of InDel markers considering low-cost genotyping with agarose gels. In order to validate these InDels, a total of 38 InDel regions were selected and primers were successfully amplified. About 13% of these InDels were in the coding sequences (CDSs) and in the 3′- and 5′- untranslated regions (UTRs). Furthermore, the efficiencies of these 16 InDel markers were assessed on 32 sesame accessions. The polymorphic information content (PIC) of these 16 markers ranged from 0.06 to 0.62 (average: 0.33). These results demonstrated the success of InDel identification and marker development for sesame with the use of ddRADSeq data. These agarose-resolvable InDel markers are expected to be useful for sesame breeders.